A minimal thrust vectoring rotor with six degree of freedom: Design and analysis. Issue 1 (30th March 2021) - Qiu, Wei; Xu, Chao
Abstract: This article presents a minimal thrust vectoring rotor (mTVR) with 6‐DoF motion ability. The mTVR is equipped with only three tiltable thrust units that deploy the coaxial counter‐propellers design for generating pure thrusts. Thus, the mTVR is able to perform 6‐DoF flight with decoupled translation and rotation based on the full rank Jacobian matrix. The geometry of the mTVR is optimised first, by studying the condition number of the Jacobian matrix that contains five geometry parameters. The overall system is then carefully modelled based on the actual hardware configuration of the mTVR prototype, including the coaxial counter‐propeller thruster, the high‐voltage servo for tilting, and the detailed multi‐rigid body motion dynamics of the vehicle. Next, the output envelop and dynamic response of the 6‐DoF actuator performance are evaluated. A 6‐DoF motion controller with disturbance rejection is designed and tested on a specialised multi‐functional software platform developed for the mTVR. The controller shows good stability in regular, even aggressive operation of the vehicle.